DNA binds to a specific site of the adhesive blood-protein von Willebrand factor guided by electrostatic interactions - Sandoval-Perez, Angelica; Aponte-Santamaria, Camilo (Nucleic acids research, 2020)
Abstract. Neutrophils release their intracellular content, DNA included, into the bloodstream to form neutrophil extracellular traps (NETs) that confine and kil